THE UTILIZING AN E-READING LOG TO ENHANCE THE READING PERFORMANCE OF EMIRATI STUDENTS - Al Hosani , Naeema (2019)
In a post-globalized era, educational technology has a profound impact on higher education pushing pedagogical boundaries toward new destinations and opening new horizons with regard to the extensive use of e-texts or other electronically accessed reading resources, such as electronic reserves or posted URLs (Buczynski, 2007; Murray & Pérez, 2011; Young, 2010). In other words, mobile information technology is transforming the education landscape by providing students with the opportunities to engage in a new kind of instruction. The growth and popularity of digital content in the form of e-books and other electronic facilities, delivered to electronic reading platforms has been significant (Hyman, Jack A. Moser, Mary and Segala, Laura N. 2014). This trend, reinforced by recent studies, which reveal the growing interest of different categories of students in electronic reading. For example, S.W. Ji et al, in their experiment surveys of 101 students -in two undergraduate college courses- discovered that respondents reported an overall preference for electronically supplied readings (Sung Wook Ji, Sherri Michaels and David Waterman, 2014, p. 17). The progress in the field of educational technology results into the utilization of electronic reading systems for digital text. Studies provide evidence that when technological advancements integrate into reading practices, they have a profound influence on student performance. (Wright, S., Fugett, A., and Caputa, F. 2013. 367). The use of electronic reading platforms, which include e-books, tablet computers, and other devices have been widely advocated by college students. Nevertheless, the adoption of such mobile information technology was recently integrated in the UAE University educational milieu. On this basis, this paper investigates the reading performance of an extended sample of students at the United Arab Emirates University in order to assess their attitudes towards print and electronic reading practices.